Some diseases are described in the literature as sometimes acute, sometimes chronic: How do general practitioners take medical decisions when faced with “fluctuating” conditions? A qualitative study - Julien Le Breton; Laura Moscova; Florence Pinsard-Laventure; Etienne Audureau; Émilie Ferrat; Pascal Clerc (PLoS ONE, 2025)
Background Although there is a clear distinction between the management of typically acute diseases (e.g., a sore throat) and the management of typically chronic diseases (e.g., diabetes), there is also a ‘fluctuating’ zone that includes many medical conditions with a major impact on the healthcare system and the management of which is usually judged to be unsatisfactory. Objective To understand how general practitioners (GPs) identify and manage acute, chronic and ‘fluctuating’ (i.e., subacute or recurrent acute) conditions on a day-to-day basis. Methods In a qualitative focus group study, 33 French GPs were invited to discuss their management of typical acute diseases, typical chronic diseases, and ‘fluctuating’ conditions. Data saturation was achieved after five focus groups. Thematic content analyses and matrix analyses (disease management key factors vs. diseases studied) were performed. Results The disease management key factors were classified into in seven themes: physician-patient negotiation; complex consultations; greater vigilance for patients with multimorbidity; the absence of standard treatments; patient education over time; inapplicable guidelines; and difficult multidisciplinary coordination. The specific management key factors of ‘fluctuating’ conditions were frequent, erratically scheduled consultations; consultations focused on social relationships, work, and the family; the lack of effective drug treatment in most cases; a break in the patient pathway; a lack of initial medical education about these diseases; and medical guidelines judged to be inappropriate with regard to actual practice. Conclusions These results challenge the acute/chronic dichotomy that is still applied to disease management but also highlight possible ways of improving the management of ‘fluctuating’ conditions.